Woman’s empowerment in mulan: a feminist literary - Rotua Sinta Marito Pakpahan; Selviana Napitupulu (Indonesian Journal Education, 2026)
Women’s empowerment has become a central theme in contemporary literary and film studies, particularly in works that challenge traditional gender roles. Mulan, in both its animated (1998) and live-action (2020) versions, presents a female protagonist who resists patriarchal expectations and redefines women’s position in society. This study aims to analyze the representation of women’s empowerment in Mulan using a feminist literary approach. The analysis focuses on how Mulan negotiates gender norms, asserts agency, and embodies feminist values through her actions, decisions, and character development throughout the narrative. Using qualitative textual analysis, the study examines key scenes, dialogues, character portrayals, and symbolic elements that illustrate empowerment, resistance, and identity construction. The findings reveal that Mulan presents empowerment through three major aspects: (1) challenging patriarchal structures, (2) redefining femininity and heroism, and (3) asserting women’s autonomy and voice. The film portrays Mulan not only as a courageous warrior but also as a symbol of women’s capacity to transcend societal limitations and participate equally in traditionally male-dominated spaces. This research contributes to feminist literary criticism by highlighting how popular films can promote gender awareness and broaden representations of empowered women in modern narratives.